2020
DOI: 10.1021/acs.inorgchem.0c01686
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Limits of Dative Boratrane Bonding: Iron as a Strong Lewis Base in Low-Valent Non-Heme Iron-Nitrosyl Complexes

Abstract: We previously reported the synthesis and preliminary characterization of a unique series of lowspin (ls) {FeNO} 8−10 complexes supported by an ambiphilic trisphosphineborane ligand, [Fe(TPB)(NO)] +/0/− . Herein, we use advanced spectroscopic techniques and density functional theory (DFT) calculations to extract detailed information as to how the bonding changes across the redox series. We find that, despite the highly reduced nature of these complexes, they feature an NO + ligand throughout with strong Fe-NO π… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 89 publications
2
16
0
Order By: Relevance
“…While the ls-{FeNO} 8 and ls-{FeNO} 10 complexes are diamagnetic, the ls-{FeNO} 9 complex is paramagnetic with a total spin of S t = 1/2. Vibrational spectroscopy (IR and NRVS) further showed that these complexes have strong Fe–NO bonds, with Fe–NO and N–O stretching frequencies of 610/583/602 cm –1 and 1745/1667/1568 cm –1 , respectively, along the ls-{FeNO} 8–10 series . Interestingly, a QCC-NCA analysis of the NRVS data revealed force constants for the Fe–B bond of 0.51/0.42/1.56 mdyn/Å for the ls-{FeNO} 8–10 series.…”
Section: Non-heme Iron Centers and Nomentioning
confidence: 99%
See 3 more Smart Citations
“…While the ls-{FeNO} 8 and ls-{FeNO} 10 complexes are diamagnetic, the ls-{FeNO} 9 complex is paramagnetic with a total spin of S t = 1/2. Vibrational spectroscopy (IR and NRVS) further showed that these complexes have strong Fe–NO bonds, with Fe–NO and N–O stretching frequencies of 610/583/602 cm –1 and 1745/1667/1568 cm –1 , respectively, along the ls-{FeNO} 8–10 series . Interestingly, a QCC-NCA analysis of the NRVS data revealed force constants for the Fe–B bond of 0.51/0.42/1.56 mdyn/Å for the ls-{FeNO} 8–10 series.…”
Section: Non-heme Iron Centers and Nomentioning
confidence: 99%
“…This result suggests that a Fe–B single bond is formed in the ls-{FeNO} 10 complex, where iron now takes on the role of the Lewis base and donates an electron pair in the d z 2 orbital to the boron Lewis acid. In this sense, the [Fe­(TPB)] platform can store two electrons in the Fe–B bond upon reduction of the iron center to the formally Fe­(-II) oxidation state, and these electrons can then be utilized for small molecule activation, for example in N 2 activation. ,,, Even though boron is not used in this regard in biology, other Lewis acids can potentially act in such a way to stabilize reactive intermediates of NO chemistry and of other small-molecule activation processes.…”
Section: Non-heme Iron Centers and Nomentioning
confidence: 99%
See 2 more Smart Citations
“…The bonding and electronic structures of P 3 B Fe–N 2 [0/1−] and (AltraPhos)­Fe–N 2 [0/1−] have previously been elucidated through spectroscopic and computational methods. , In short, the bonding in these complexes is best described as involving an Fe → X­(III) dative interaction where the apical Lewis acidic atom serves to lower the energy of the σ­(Fe–X) orbital of Fe d z 2 and X p z parentage below that of the d xy , x 2 – y 2 set in a typical trigonal bipyramidal orbital scheme. Therefore, reduction of 3 to 4a / 5a and 6 to 7 is primarily Fe centered, giving rise to formally Fe­(−I) species with electronic configurations (d xz , yz ) 4 (σ­(Fe–X)) 2 (d xy , x 2 – y 2 ) 3 and a substantial Fe-to-X backbond …”
Section: Resultsmentioning
confidence: 63%